Florida Fresh: Cabbage - Jennifer Hillan (EDIS)
This document is FCS8676, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.